Prediction and Analysis of Transient Electric Field in DC Yard of Flexible Converter Station Under Short-Circuit Conditions - Sihang WU; Hong SHEN; Lei QI; Peng QIU; Zhaoxia KUAI (Zhongguo dianli)
In the case of short-circuit fault, the flexible DC converter station would produce transient yet strong electromagnetic field, which would impact on the secondary equipment in the converter station. In this paper, the problem of electric field disturbance at the secondary equipment in the short circuit test of Dinghai converter station was studied systematically. The potential of the key nodes in the DC field was analyzed, and 3D model of the equipment in the DC field was established. Considering the time-varying topological structure of the DC circuit breaker, the potential function of each node in the DC field was taken as the first boundary condition of the electric quasi-static field solution area, and the electric field distribution of the secondary equipment around the DC circuit breaker under three kinds of short-circuit conditions was calculated accordingly. The following facts were revealed by the simulation results: the maximum electric field strength is 33 kV/m; the maximum rise and fall edge is 40 μs; the electric field strength could be determined by the spatial layout and voltage amplitude; and the electric field strength waveform would be consistent with the rise and fall edge of the voltage waveform.